Trend and Correlates of Leadership Competencies Among Female Health Professionals in Albania - Caushaj, Klevis; Czabanowska, Katarzyna; Roshi, Enver; Muja, Herion; Burazeri, Genc (Frontiers in Public Health, 2019)
Aim: Our aim was to assess the trends and correlates of the leadership competency level of female health professionals in Albania, a transitional country in the Western Balkans, based on a standardized international instrument. Methods: Two nationwide cross-sectional studies were conducted in Albania in 2014 (first wave; n = 105 women) and subsequently in 2018 (second wave; n = 121 women). A structured questionnaire was administered to all female participants aiming at self-assessing the current level of leadership competencies and the required (desirable) level of leadership competencies for their current job position. The questionnaire consisted of 52 items pertinent to eight domains. Answers for each item of the instrument ranged from 1 (“minimal competency level”) to 5 (“maximal competency level”). Overall summary scores (range: 52–260) were calculated for both the current and the required leadership competency levels in both survey rounds, based on which the gap in leadership competency level was also computed (required minus current competency level). Binary logistic regression was used to assess the correlates of the gap in leadership competency level among study participants. Results: In multivariable-adjusted logistic regression models, there was evidence of a positive association between the gap in leadership competency level and: workplace in urban areas (OR = 3.2, 95%CI = 1.6–6.6); work experience (OR[for 1 year increment] = 1.1, 95%CI = 1.0–1.2); first round of the survey conducted in 2014 (OR = 2.1, 95%CI = 1.0–4.3); and, particularly, a high managerial job position/level (OR = 3.8, 95%CI = 1.6–9.3). Conversely, there was an inverse relationship with the age of women (OR[for 1 year increment] = 0.9, 95%CI = 0.8–1.0). Conclusion: Our study provides useful evidence about trends over time and selected correlates of the gap in leadership competencies among female health professionals in Albania. Policymakers and decision-makers in Albania and other countries should be aware of the unmet need for leadership training of female health professionals at all levels.